Model-Based Assessment of Heavy Metals Leaching Behavior in Wasted Activated Sludge Utilization - Maulidiany, Nopa Dwi; Oktovidonna, Sabina Adwina; Rastandi, Jessica Dorothea; Lokahita, Baskoro; Abdillah, Ayik (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
Advanced sludge treatment remains a critical challenge as global wastewater production increases, with waste-activated sludge (WAS) posing ecological and health risks due to heavy metal accumulation. This study characterized WAS based on solid parameters and metal content, focusing on As, Cd, Cr, Cu, Fe, Pb, Ni, Mg, Mn, and Zn, which exceed organic fertilizer thresholds. Using Visual MINTEQ, heavy metal leaching behavior was modelled under pH-independent and pH-dependent conditions. The pH-independent simulation identified As as the least leachable metal (2.166 × 10⁻¹³ mgAs/L) and Cu as the most leachable (1.261 × 10⁻⁴ mgCu/L). The pH-dependent simulation (pH 1.5–13.5) revealed significant leaching for Fe (21.777 mgFe/L) and Cu (1.98 ×10-3 mgCu/L), with Ni (0.120 mgNi/L) and Pb (2.7 × 10-4 mgPb/L) posing chronic risks to aquatic ecosystems. Metals like Cr, Cd, and Ni exhibited distinct leaching patterns influenced by pH and WAS composition. The findings highlight the critical role of pH, along with WAS composition, in governing heavy metal leaching, providing insights to mitigate risks and support sustainable sludge management practices.